Pembuatan Video Animasi 2 Dimensi Sebagai Media Pembelajaran Pengenalan Perangkat Komputer Untuk Sekolah Dasar - Yuly, Ade Rahma (MULTINETICS, 2023)
Learning media is an essential factor in the success of learning activities in education. The delivery of computer equipment introduction material at SDN 02 Pisangan still uses PPT material and traditional learning methods using books and blackboards. This method is considered less than optimal in delivering material and creates a tendency to get bored when students read the material. Learning media should be able to keep up with existing technological developments. Animation can be an example of developing conventional learning media. Therefore, this study aims to make a 2-dimensional animated video in which there is an introduction to computer devices such as mice, keyboards, and monitors for elementary school students. This study uses a Research and Development (R&D) approach with a design thinking model consisting of empathize, define, ideate, prototype, testing, and implement stages. Meanwhile, the MDLC (Multimedia Development Life Cycle) method is used at the prototyping stage. At the testing stage, using a questionnaire calculated with a Likert scale and interviews, the results obtained strongly agreed that animated videos in applications can help ICT learning.